Note on natural infection of the Calomys expulsus, Lund, 1841 (Cricetidae-Rodentia) by Trypanosoma cruzi - Mello, Dalva A.; Teixeira, Maria Lúcia (Revista de Saúde Pública, 1977)
A strain of T. cruzi was isolated from the wild rodent Calomys expulsus, Lund, 1841, captured in the northeastern part of the county of Formosa, state of Goiás This strain was isolated through inoculations into laboratory animals and subsequent xenodiagnosis with R. neglectus, T. infestans and P. megistus. This strain has low pathogenicity for the inoculated animals but develops resistance against reinfection with the Y strain of T. cruzi. Blood trypanosomes have a mean total length of 21.8 µ and the nuclear index was 1.15.